2019
DOI: 10.2147/ccide.s205144
|View full text |Cite
|
Sign up to set email alerts
|

<p>Disinfection of dental impressions: knowledge and practice among dental technicians</p>

Abstract: Background: Dental impressions are a common source for transmission of infection between dental clinics and dental labs. Dental impressions can be cross-contaminated by patient’s saliva and blood, which then cross-infect the dental casts poured from the impressions. Objective: To evaluate the current practices of disinfection of dental impressions and their protocols and to assess the knowledge of cross-infection control among dental technicians in Jordan. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 9 publications
(11 reference statements)
1
34
0
9
Order By: Relevance
“…This is a positive finding when compared to a similar type of study, where the investigators reported the poor compliance of dental technicians in using protective barriers. 14 Proper disposal of laboratory waste is a vital factor in infection control. Impression materials amount to 30% of the total solid waste generated in dental practice.…”
Section: Discussionmentioning
confidence: 99%
“…This is a positive finding when compared to a similar type of study, where the investigators reported the poor compliance of dental technicians in using protective barriers. 14 Proper disposal of laboratory waste is a vital factor in infection control. Impression materials amount to 30% of the total solid waste generated in dental practice.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Best practice is not always followed as 72% of impressions received at a Swedish dental laboratory yielded bacterial growth and a questionnaire survey of laboratory technicians in Jordan reported that 71% of respondents did not receive labelled impressions from dentists and were thus uninformed regarding disinfection status of impressions. 2,18 Consequently, some of the responding laboratories disinfected the impression upon receipt, mainly by spraying. 18 The effectiveness of various spray disinfectants with different concentrations and contact time on irreversible hydrocolloid impression materials (alginate) found that not all the ADA-approved concentrations of surface disinfectants work equally well.…”
Section: Introductionmentioning
confidence: 99%
“…2,18 Consequently, some of the responding laboratories disinfected the impression upon receipt, mainly by spraying. 18 The effectiveness of various spray disinfectants with different concentrations and contact time on irreversible hydrocolloid impression materials (alginate) found that not all the ADA-approved concentrations of surface disinfectants work equally well. Diluted sodium hypochlorite (0.5%) was very effective against S. aureus, S. viridans and B. subtilis, while a 5.25% concentration of sodium hypochlorite was the most effective disinfectant overall and required the shortest contact time of 1 min.…”
Section: Introductionmentioning
confidence: 99%
“…The potential risk of contamination with the aerosols and pathogens exists during all dental procedures encompassing trimming, finishing, and polishing, so there is a need for appropriate disinfection techniques which act efficiently on a broad spectrum of microorganisms and are cost-effective, rapid and safe for human's health. [2][3][4][5] The disinfection of the dental impressions is strongly recommended by the health policymakers such as the Centre for Disease Control (CDC), the American Dental Association (ADA) and the British Dental Association (BDA) to prevent the possible transmission of infectious diseases and cross-contamination. [6][7][8] Although guidelines for sterilization and disinfection have been established by these organizations, investigations have shown that proper practice is not always followed.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Although guidelines for sterilization and disinfection have been established by these organizations, investigations have shown that proper practice is not always followed. 5 Nowadays immersion in chemical disinfection agents has been mainly suggested for disinfecting dental prostheses like acrylic resin dentures. These disinfectants include a wide variety of chemicals such as 2% alkaline glutaraldehyde, 0.5% and 1% sodium hypochlorite, 3% aqueous formaldehyde, hydrogen peroxide, 1% sodium hypochlorite, 4% chlorhexidine gluconate, and 3.78% sodium perborate.…”
Section: Introductionmentioning
confidence: 99%